Atypical form of transient acantholytic dermatosis with edematous erythema (Dermatology Reports, 2023)
Dear Editors, Transient acantholytic dermatosis, also called Grover’s disease, is a benign acquired disorder with a transient course. The typical clinical presentation is the erythemato-papular form; cases presenting with edematous erythema without papules are extremely rare...